The phantom in the mirror - Erickson, John R., 1943-; Holmes, Gerald L. (New York : Viking, 2000)
Hank the Cowdog investigates reports of a phantom dog on the ranch.
Previously published: Houston, Tex. : Maverick Books, c1993.
Keywords: Dogs -- Fiction; Ranch life -- West (U.S.) -- Fiction; Humorous stories..; Mystery and detective stories; West (U.S.) -- Fiction